Government debt management in developing and emerging market countries - Panizza, Ugo (Henry Stewart Talks, 2009)
External versus domestic public debt: definitions and recent evolution, The risks of sovereign finance, Domestic and international policies for reducing the risks of sovereign finance, How to build domestic bond markets, How to deal with debt crises